Kualitas Pelayanan Terhadap Kepuasan Dan Loyalitas Nasabah Pada Bank Xyz - Khoerul Umah (Universitas Tarumanagara, 2019)
Communities are increasingly selective in choosing banking services to place their own funds in order to avoid the risk of loss due to poor performance of a bank. Quality services can increase the satisfaction and loyalty of the company so it is expected to encourage the company's success to win the competition. This study aims to analyze the effect of service quality variables consisting of dimensions of reliability, responsiveness, assurance, empathy, and physical evidence of customer satisfaction and loyalty. Data analysis used multiple linier regression analysis method with 100 bank customer XYZ sample as respondent. The sampling technique using simple random sampling. Validity and reliability tests are used in testing of research instruments as well as testing classical assumptions in the form of normality test, heterokedastisity test, and linearity test. The results showed that the quality of service has a positive and significant impact on loyalty through customer satisfaction and satisfaction have a positive and significant impact on customer loyalty.